2013
DOI: 10.1016/j.prevetmed.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of the French human Salmonellosis cases to the main food-sources according to the type of surveillance data

Abstract: Salmonella are the most common bacterial cause of foodborne infections in France and ubiquitous pathogens present in many animal productions. Assessing the relative contribution of the different food-animal sources to the burden of human cases is a key step towards the conception, prioritization and assessment of efficient control policy measures. For this purpose, we considered a Bayesian microbial subtyping attribution approach based on a previous published model (Hald et al., 2004). It requires quality inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Food animals are known to be reservoirs for foodborne pathogens, therefore food products from these animals could be considered a threat to the safety of the food supply chain, putting humans at risk of contracting salmonellosis (David et al, 2013;Gorski et al, 2011;Ishihara et al, 2009;Wahlström, Andersson, Plym-Forshell, & Pires, 2011). Perpetuation of pathogens in the environment may exacerbate the risk of salmonellosis as well from direct exposure through occupational practices (LeJeune & Kersting, 2010;Saeed & Hamid, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Food animals are known to be reservoirs for foodborne pathogens, therefore food products from these animals could be considered a threat to the safety of the food supply chain, putting humans at risk of contracting salmonellosis (David et al, 2013;Gorski et al, 2011;Ishihara et al, 2009;Wahlström, Andersson, Plym-Forshell, & Pires, 2011). Perpetuation of pathogens in the environment may exacerbate the risk of salmonellosis as well from direct exposure through occupational practices (LeJeune & Kersting, 2010;Saeed & Hamid, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…from clinically ill animals should be avoided, since they are not representative of the animal population surveyed and sick animals should not be used for food production. However, such isolates are usually incidental findings, present alongside other primary pathogens and studies have shown that diagnostic isolates can be valuable for both outbreak investigation and source attribution, since similar isolates can be found sub-clinically in the healthy animal population (David et al, 2013).…”
Section: Animal Datamentioning
confidence: 99%
“…Modification of the prior specification for the subtype-dependent parameters was also done in order to avoid assuming similarity between some subtype parameters, which was done in the original Danish model to circumvent overparameterisation. Similarly, David et al (2013) have proposed to specify the subtype-dependent factors for subtypes occurring in only a single source as a constant value thereby improving convergence of the model. Finally, Mullner et al (2009) and Pires and Hald (2010) included time period as a dimension in the model, thereby making the estimation of the subtypes-depending parameters more robust.…”
Section: Frequency-matching Modelsmentioning
confidence: 99%